INTEGRAÇÃO BIM POR MEIO DA METODOLOGIA IDM/MVD PARA A ANÁLISE ESTRUTURAL, CONSIDERANDO O SISTEMA CONSTRUTIVO DE WOOD-FRAME - Fairbanks, José; Messias, Giovane; Moreira, Pedro; Correa, Fabiano (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
There are many ongoing initiatives to adopt Building Information Modeling (BIM) processes in Brazil. Small and medium companies need to investigate how their current methods should change so that BIM could be effectively implemented, before incurring expenses with software acquisitions. In addition, it will be good practice to use OpenBIM standards, such as Industry Foundation Classes (IFC) data schema to integrate different workflows occurring during the lifecycle of the building. Through the constructive research approach, it will be elaborated the Information Delivery Manual (IDM), which will be the base for a Model View Definition (MVD, related to the proposition of integrating, via BIM, the process inherent to the structural analysis. The IDM/MVD is a methodology adopted by buildingSMART to help the development of software integration with open standards. As a final product, an MVD will establish which are the entities that should be present in the models, and what kind of information should be given for each attribute or property. The documentation will be validated by the wood-frame construction system used by Tecverde, a company located in Curitiba (PR). Results of this ongoing master research are presented herein.